The Socioeconomic Vulnerability of Linemen in Pakistan’s Electricity Distribution Sector: A Sociological Analysis of Labor Inequalities - Arif, Muhammad; Sabir, Imran (Pakistan Journal of Humanities and Social Sciences, 2025)
Linemen in Pakistan’s electricity distribution sector play an important and vital role to ensure unintrepted and smooth power supply to the consumers. To maintain electricity supply, they work under severe health and safety conditions. They face hazardous environments, wage disparities, job insecurity and weak labor protections. This study deals with socioeconomic and occupational inequalities between contractual and permanent linemen in a sociological lense. Findings reveal that contractual linemen earn 40% less than permanent workers in Punjab. They are experiencing significantly high workplace injury, disbility and fatality. Weak regulatory enforcement and employer driven approaches have worsen labor conditions. They are facing socioeconomic inequality and severe work conditions. Comparative labor analysis highlights that developed countries offer stronger worker protection, health and work safetyresulting reduction in workplace fatalities of the linemen. This study digout policy reforms to improve workplace safety of the linemen working in Pakistan electricity distribution sector. This also suggests wage parity and establish employer responsibility to secure the precious lives of linemen.